Factors and Conditions that Influence Teenage Pregnancy among In-school Adolescents in Umuahia North Local Government Area (L.G.A) of Abia State, Nigeria - Elekeh,, Rosemary Ichita; Enwereji,, E.E; Odina,, Chinyere (International Journal of Health Statistics, 2021)
Introduction Adolescence is a critical stage in human development that is characterized by peer pressure, confusion, exuberance and experimentation, particularly with sexual relationships. This is why attention should be paid to adolescents’ reproductive health issues so as to reduce their exposure to aggressive sexual activities which could expose them to sexually transmitted diseases, unwanted pregnancies and others. This study aimed at reducing the factors and conditions that influence teenage pregnancy among in-school adolescents in Umuahia North LGA of Abia State. Materials and Methods The study used a cross sectional descriptive study. A randomly selected sample of 416 adolescents between the ages of 13-19 years were studied. Structured self-administered questionnaire was used for data collection. Descriptive statistics, using frequencies, percentages and means were utilized for data analysis. Results The study found that 198 (47.6%) of the respondents were sexually active and that 89 (45%) of them had been pregnant. More than half 103 (52%) of the study group indicated that peer pressure influenced their sexual activities. About 46(51.7%) of the adolescents said they were pregnant so as to keep the new born baby with motherless babies homes. Conclusion Therefore, there is need for increased sex education for in-school adolescents so as to highlight the effects of teenage pregnancy on adolescents.
Keywords: adolescents; pregnancy; peer pressure and sexually transmitted infections